Classroom disruptions in digital teaching during the pandemic – an interview study - Meinokat, Pierre; Wagner, Ingo (Frontiers in Education, 2024)
The pandemic increased the speed at which education had to evolve into the digital age. While digital tools create possibilities, new forms of classroom disruptions appear. Classroom disruptions as essential part of classroom management may take away students' precious learning time and the associated stress could put teachers' health at risk.We conducted a semi-structured, guideline-based interview study with teachers from Germany and asked them about experienced disruptions in digital teaching (RQ1), their prevention and intervention strategies (RQ2) as well as their opinions on potentials and risks of the digital evolution in teaching (RQ3).Findings: Findings show that digital teaching is affected by already known and by new types of disruptions. Teachers use their existing experiences to adapt to these new challenges. Simultaneously they reflect on the changes in teaching due to the increased digital involvement and identify potentials for improved teaching in the future.Discussion: Based on the research literature and our interview findings a two-dimensional graph of classroom disruptions is developed to systematize disruptions in context of digitalization.